Samuel Brugger diaries and genealogy - Brugger, Samuel, 1830-1903.
Diaries kept by Brugger relating chiefly to his work as a farmer, railroad engineer, and schoolteacher living in Unionville, Pa. Subjects include local schools; the Methodist Church; the migration of birds; Brugger's collection of minerals, plants, and preserved animals; natural history; and railroads. Brugger discusses his work as railroad surveyor as well as his work as engineer on the construction of the Boston, Hartford, and Erie Railroad Company; the Western Maryland Railroad Company; and the Bald Eagle Valley Railroad Company which was built during the Civil War. Includes a genealogy (1947) of the Brugger family originating in Switzerland.
In part, positive photocopy.
Civil engineer and farmer.
Collection material in English.
Keywords: Brugger family; Bald Eagle Valley Railroad Company; Boston, Hartford, and Erie Railroad Company; Western Maryland Railroad Company; Agriculture -- Pennsylvania; Animals; Birds -- Migration; Education -- Pennsylvania -- Unionville; Genealogy; Methodist Church; Minerals; Natural history; Plants; Railroads -- Surveying; Railroads -- Connecticut; Railroads -- Maryland; Railroads -- Pennsylvania; Railroads -- New York (State); Railroads -- Rhode Island; Railroads -- United States; Schools -- Pennsylvania -- Unionville; Zoological specimens; Switzerland -- Genealogy; United States -- Genealogy; United States -- History -- Civil War, 1861-1865 -- Transportation; Civil engineers; Farmers